Reproducibility of Optical Coherence Tomography Angiography Macular and Optic Nerve Head Vascular Density in Glaucoma and Healthy Eyes. Issue 10 (October 2017) - Manalastas, Patricia I.C.; Zangwill, Linda M.; Saunders, Luke J.; Mansouri, Kaweh; Belghith, Akram; Suh, Min Hee; Yarmohammadi, Adeleh; Penteado, Rafaella C.; Akagi, Tadamichi; Shoji, Takuhei; Weinreb, Robert N.
Abstract : Purpose: Optical coherence tomography angiography (OCT-A) is a noninvasive technology that allows visualization of retinal blood vessels. It is important to determine reproducibility of measurements as low precision can impair its diagnostic capabilities. The purpose of this study is to determine intravisit and intervisit reproducibility of optic nerve head (ONH) and macular vessel density measurements with OCT-A. Patients and Methods: Fifteen healthy volunteers and 14 glaucoma patients completed 2 OCT-A (AngioVue; Optovue Inc.) scanning sessions on each of 2 separate days to assess intravisit and intervisit reproducibility. A series of ONH and macula scans were acquired at each session. Vessel density (%), the proportion of vessel area over the total measurement area was calculated. Reproducibility was summarized using coefficients of variation (CV) and intraclass correlation coefficients calculated from variance component models. Results: In healthy eyes, the CV of intravisit and intervisit global vessel density measures ranged from 1.8% to 3.2% in ONH scans and 2.5% to 9.0% in macular scans. In glaucoma eyes, the CV of intravisit and intervisit global vessel density measures ranged from 2.3% to 4.1% in ONH scans and 3.2% to 7.9% in macular scans. CVs were lower for global than sectorial measures. Global OCT-A ONH intraclass correlation measurements for the retinal nerve fiber layer in healthy eyes were lower (range: 0.65 to 0.85) than in glaucoma eyes (range: 0.89 to 0.94). Scan size did not make large differences in measurement CVs. Conclusions: Reproducibility of OCT-A ONH and macula vessel density measurements is good. Moreover, glaucoma patients have sparser vessel density with poorer reproducibility than healthy subjects.